ANALYSIS OF ARABIC VOCABULARY (MUFRODAT) LEARNING FOR THE DEVELOPMENT OF ARABIC SPEAKING SKILLS AMONG SECOND GRADE MTS STUDENTS AT ALFATIH INSANI MODERN ISLAMIC BOARDING SCHOOL. - Aulia Susanti; Zahrodin Fanani (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to examine the effectiveness of Arabic vocabulary (mufrodat) learning in improving the speaking skills of second-grade students at MTs Pondok Pesantren Modern Alfatih Insani. The background of this research is based on the low mastery of vocabulary and students’ speaking abilities, compounded by a learning environment that has not fully supported the creation of an Arabic-speaking atmosphere. The research employed a descriptive qualitative method, with data collected through observation and interviews. The subjects of the study consisted of an Arabic language teacher and ten second-grade students.The findings indicate that vocabulary learning was conducted through talaqqi and memorization methods, supported by simple media such as a whiteboard, a pocket dictionary, and speakers. Students’ responses showed gradual improvement in their speaking ability, as observed through teacher interviews during Arabic learning activities. Nevertheless, challenges were identified, including low student motivation and a learning environment that was less conducive to fostering Arabic language habituation. The study concludes that vocabulary learning can enhance students’ speaking skills if supported by appropriate methods and a conducive learning environment.